Pengetahuan dan Kepatuhan Ibu Hamil Trimester III Dalam Konsumsi Tablet Tambah Darah di Puskesmas Beringin Raya Kota Bengkulu - Anisah Tifani Maulidyanti; Edhyana K Sahiratmadja (Jurnal Kebidanan Harapan Ibu Pekalongan, 2023)
Anemia during pregnancy is associated with an increased risk of preterm birth, low birth weight, and bleeding. The National Program for the provision of 90 Blood Supplement during pregnancy has been implemented to reduce the incidence of anemia. Based on Riskesdas 2018, the proportion of iron tablets taken was 74.52% for giving <90 tablets. The iron tablets program is still not effective due to insufficient knowledge and low adherence. This study aims to describe the knowledge of pregnant women regarding anemia and adherence of Blood Supplementary Tablets consumption at the Beringin Raya Health Center, Bengkulu City. This study used a descriptive survey method with a cross sectional approach. Sampling technique with purposive sampling. This study describes the knowledge of pregnant women regarding blood supplement tablets consumed during pregnancy. The results showed the majority of pregnant women had knowledge about anemia, the sufficient category, 29 respondents (73%), the less category, 7 (17%), the good category, 4 respondents (10%). Compliance in taking iron tablets with low category 27 respondents (68%), medium category 8 respondents (20%), high category 5 respondents (12%). This research is expected to illustrate the knowledge and compliance of pregnant women is still low regarding anemia and iron supplement tablets.